Effectiveness of music therapy on cancer patients undergoing chemotherapy - 최정옥; 노기옥 (International Journal of Advanced Culture Technology(IJACT), 2025)
This is a randomized controlled trial to determine the effects of music therapy (Healing Beat) linked to an individual's heart rate on anxiety, stress, autonomic nervous activity, blood pressure, and heart rate in cancer patients undergoing chemotherapy. Data were collected from December 20, 2019 to February 20, 2020, and a total of 61 patients undergoing chemotherapy in the one university hospital were randomly assigned to the experimental group (n=31) and the control group (n=30). The experimental group was provided with music (healing beats at a BPM equal to their own heart rate) for 30 minutes, while the control group was placed in a quiet environment without music. The collected data were analyzed by independent t-test and repeated measures of ANOVA using IBM SPSS/WIN 24.0 program. The results of this study showed that the anxiety of the experimental group was significantly reduced compared to the control group (t=-6.00, p=<.001), and it was found to be effective in reducing stress (F=3.46, p=.002). In addition, the experimental group showed a significant reduction in heart rate compared to the control group (F=5.36, p= <.001).Therefore, the music therapy (Healing Beat), which provides beats based on an individual's heart rate, could be expanded in a variety of settings as a nursing strategy to reduce anxiety and stress in cancer patients.